The rise of social media marketing during Covid - Jooste, Stephanie (The IIE, 2022)
The purpose of this qualitative research report was to gain a better understanding of South African consumers buying behaviour based on the online experience curated by brands via social media platforms such as Facebook, Instagram, Twitter and TikTok, post the Covid-19 outbreak. Despite conducting an extensive literature review on consumer behaviour models as well as placing these within a digital context there were no academic research articles which sought to understand the experience of consumers as well as brands during Covid. Hence, the reason for the research conducted was to gain a better understanding and make a meaningful contribution as to how brands can successfully communicate with consumers on the above-mentioned digital platforms during such unprecedented times. Focus groups were conducted with 14 conveniently sampled participants (both consumers and industry-professionals/brand owners), at which data saturation was reached. A thematic analysis was used to code the transcribed data. The process followed was inductive and once data saturation was reached, codes and themes were collated/developed. Findings indicated that consumer behaviour has shifted during Covid, in terms of what they prioritise their spending on, which platforms they spend most of their time on as well as which platforms they prefer brands to interact and engage with them on, and what type of brand communications are most appealing to them.
An exploratory study of consumer buying behaviour based on the online experience curated by brands
Keywords: Consumer behaviour; Covid-19; Digital marketing; Online shopping; Buying patterns